Terms of Intentionality in Early Prajñāpãramitā Texts (“Phenomenal Reality” (dmigs pa), “Abiding” (gnas pa) and “Practice” (spyod)) - Korobov, Vladimir (Acta Orientalia Vilnensia, 2002)
The paper focuses on the connection of some Prajñāpãramitā terms with the conception of intentionality as it is presented in modern phenomenology. Three terms: dmigs pa - “phenomenal reality”, gnas pa - “abiding” and spyod - “practice” are taken to demonstrate specific intentional context of Prajñāpãramitā teaching. The interpretation of these terms in the context of a whole teaching shows that the culmination of all Prajñāpãramitā phenomenology is the access to the state beyond intentional constructions and representations. The teaching itself is not a presentation of a new ontology but a “leveling” of the field of present awareness which is deformed by intentional references.